Stereoselective Bioreduction of α-diazo-β-keto Esters - Sergio González-Granda; Taíssa A. Costin; Marcus M. Sá; Vicente Gotor-Fernández (Molecules, 2020)
Diazo compounds are versatile reagents in chemical synthesis and biology due to the tunable reactivity of the diazo functionality and its compatibility with living systems. Much effort has been made in recent years to explore their accessibility and synthetic potential; however, their preparation through stereoselective enzymatic asymmetric synthesis has been scarcely reported in the literature. Alcohol dehydrogenases (ADHs, also called ketoreductases, KREDs) are powerful redox enzymes able to reduce carbonyl compounds in a highly stereoselective manner. Herein, we have developed the synthesis and subsequent bioreduction of nine α-diazo-β-keto esters to give optically active α-diazo-β-hydroxy esters with potential applications as chiral building blocks in chemical synthesis. Therefore, the syntheses of prochiral α-diazo-β-keto esters bearing different substitution patterns at the adjacent position of the ketone group (N3CH2, ClCH2, BrCH2, CH3OCH2, NCSCH2, CH3, and Ph) and in the alkoxy portion of the ester functionality (Me, Et, and Bn), were carried out through the diazo transfer reaction to the corresponding β-keto esters in good to excellent yields (81−96%). After performing the chemical reduction of α-diazo-β-keto esters with sodium borohydride and developing robust analytical conditions to monitor the biotransformations, their bioreductions were exhaustively studied using in-house made Escherichia coli overexpressed and commercially available KREDs. Remarkably, the corresponding α-diazo-β-hydroxy esters were obtained in moderate to excellent conversions (60 to >99%) and high selectivities (85 to >99% ee) after 24 h at 30 °C. The best biotransformations in terms of conversion and enantiomeric excess were successfully scaled up to give the expected chiral alcohols with almost the same activity and selectivity values observed in the enzyme screening experiments.